An ecological review of the WGEEP report (2011) and environmental management planning in India. Issue 6 (19th August 2014) - Puyravaud, Jean Philippe; Davidar, Priya; Leal-Filho, Walter; Platje, Joost
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The Ministry of Environment and Forest, Government of India, set up the Western Ghats Ecology Expert Panel (WGEEP) in March 2010 to provide guidelines for improved management within the Western Ghats biodiversity hotspot. The WGEEP's Mandate was to identify Ecologically Sensitive Areas (ESAs). The Panel submitted their Report in 2011 but it remained unimplemented. It was not clear whether the delay was due to the unwillingness of civil society to accept ambitious environment management plans, or whether the Report had shortcomings. Design/methodology/approach We undertook a critique of the WGEEP Report and its Mandate, to evaluate key issues that could have prevented its implementation. Findings Our analysis indicated that (i) the WGEEP Mandate was ill-defined, and (ii) the WGEEP Report identified ESAs without providing a working definition. The absence of critical review of earlier environment management failures, the delayed dialogue with civil society, the absence of legislative foundation upon which such a management plan could be implemented, and the vague definition of ESAs were possibly the reasons for the unease among various stakeholders. Originality/value Our paper stresses that in order for large-scale biodiversity management projects to succeed, it is important that (i) the civil society understands the project's objective before its initiation, (ii) stakeholders are formally involved alongside ecological experts, and (iii) that methods are critically reviewed. The lack of acceptance of the Report cannot be dismissed only as a rejection of enlightened practices.